2019
DOI: 10.1111/cas.14075
|View full text |Cite
|
Sign up to set email alerts
|

Potentials of C‐C motif chemokine 2–C‐C chemokine receptor type 2 blockers including propagermanium as anticancer agents

Abstract: Inflammation plays an essential role in the development and progression of most cancers. Chemokine C‐C motif chemokine 2 (CCL2) and its receptor C‐C chemokine receptor type 2 (CCR2) constitute a key signaling axis in inflammation that has recently attracted much interest on the basis of evidence showing its association with cancer progression. Propagermanium (3‐oxygermylpropionic acid polymer) is an organogermanium compound that is given for the treatment of hepatitis B in Japan and which inhibits the CCL2‐CCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 60 publications
(80 reference statements)
3
31
0
Order By: Relevance
“…In addition, PG also has therapeutic effects in other inflammatory disease such as atherosclerosis. 38 In our study, we first confirmed that PG plays a neuroprotective role in hemorrhagic stroke. The present results showed that PG significantly reduced the permeability of the BBB, relieved brain edema by increasing the protein expression of ZO-1 and inhibited the p38 MAPK signaling pathway.…”
Section: Discussionsupporting
confidence: 73%
“…In addition, PG also has therapeutic effects in other inflammatory disease such as atherosclerosis. 38 In our study, we first confirmed that PG plays a neuroprotective role in hemorrhagic stroke. The present results showed that PG significantly reduced the permeability of the BBB, relieved brain edema by increasing the protein expression of ZO-1 and inhibited the p38 MAPK signaling pathway.…”
Section: Discussionsupporting
confidence: 73%
“…Several clinical trials of CCL2 inhibitors have been undertaken for therapeutic intervention in solid malignancies . In a mouse model, Bonapace et al found that the interruption of treatment with anti‐CCL2 neutralizing Ab led to enhanced metastasis due to an influx of monocytes into the metastatic site and a rebound of IL‐6 levels .…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical trials of CCL2 inhibitors have been undertaken for therapeutic intervention in solid malignancies. 8,9 In a mouse model, Bonapace et al found that the interruption of treatment with anti-CCL2 neutralizing Ab led to enhanced metastasis due to an influx of monocytes into the metastatic site and a rebound of IL-6 levels. 23 In conclusion, this study of PG as monotherapy in BC patients has shown a manageable safety profile and provides a basis for exploring the clinical use of PG as an antimetastatic drug for BC patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations